The analysis of opinions and attitudes of students of nursing with respect to the observance of patient’s rights in Poland - Belowska, Jarosława; Panczyk, Mariusz; Sienkiewicz, Zofia; Kaczyńska, Anna; Zarzeka, Aleksander; Gotlib, Joanna (Polish Journal of Public Health, 2015)
Introduction. As these define the status of the patient during the provision of health services, patients’ rights are a very important component of Poland’s medical law. The observance of these rights is a prerequisite for the proper performance of the nursing profession. Theoretical and practical preparation in this area is thus already a necessity in the students’ education process.Aim. The aim of the study was to analyze the opinions and attitudes of nursing students with respect to problems in the field of the observance of the rights of patients in Poland.Material and methods. The study was built upon the opinions expressed by 375 students (362 women and 13 men) of the first and second year. These were full-time and part-time students in master’s studies in nursing, of the Faculty of Health Science, Medical University of Warsaw. The study employed a qualitative and quantitative analysis of the content of essays.Results. The results of the study indicate that 59 percent of the respondents report being frequent witnesses of violation of patient’s rights. In particular, that which noted were the rights to privacy and dignity (98%), to receive sought-after information (91%) and to suitable health-care (85%). Another right seen to have been violated in the respondents’ workplace was the patient’s right to the maintenance of the confidentiality of patient-related information by medical personnel (77%).The respondents, while seeing violation of the patient’s rights by other employees, declared their own adherence to these rights in their own professional practice.Conclusions. 1. The majority of the study group repeatedly witnessed violation of patients’ rights. It would, therefore, be advisable to monitor the observance of the rights of patients by medical personnel, and to see to the professional liability of those who flagrantly breaking the law. 2. Research findings indicate that ethics should be given more emphasis in teaching future health professionals in the course of their medical studies. 3. The analysis of the available literature and our own study show that the share of medical personnel in providing information about the patients’ rights is minimal. It would be advisable for medical personnel to be given an opportunity to acquire new skills and competences in this field. 4. Awareness of the existence and knowledge of the patient’s rights, not only among medical students and health professionals, but also among patients, is crucial to their observance by the former and their exercise by the latter. It should, therefore, be spread and raised. 5. Training and thematic courses in patient’s rights should be provided in order to enable medical personnel to acquire new skills and competences in this field, with the end result of improving their observance of patient’s rights. 6. A qualitative analysis constitutes an innovative and effective way of carrying out research and interpreting research findings, being a valuable and reasonable method of conducting a survey, and in exploring the attitudes of students and health-care workers towards patient’s rights.